Diaspora Engagement Strategies and Policies - Jovan Filipovic; Srečko Srečko Devjak; Bogomil Ferfila (Central European Public Administration Review)
Diasporas have been making contributions to their motherland for a long time (Ionescu, 2006), without waiting for policies to rally them and, if truth be told, very often finding them to be the major obstacles for establishing the partnership. However, diaspora-motherland partnership is closely related to institutional frameworks, socio-economic settings, political milieu as well as issues of perceptions, images, trust and social identification, in both the home and host country, most of which are within the scope of public administration. Moreover, the evolution of policy awareness and a thorough understanding of the diaspora and development nexus are, in some countries, the result of the efforts of public administration. The development of diaspora strategies is essential because it demonstrates how state agencies, policy makers and individual citizens themselves have begun to think beyond national borders and make efforts to build non-territorial forms of organisation, such as Diaspora Virtual University. Promotion of networks, strategic alliances and sustained institutional cooperation between diaspora and the policy makers such as the Ministries for Diaspora, as well as other officials dealing with diaspora and development related issues have become the subject of primary interest in many countries, one of them being Serbia. As a part of the effort to formulate effective and just policies used to respond to the brain drain, the paper analyses and recommends different policy types. Among different models of academic diaspora congregation is, no doubt, the alumni model, which proved to be very useful for both, developed and developing countries. The paper presents the concept as a part of the »brain gain« model and states the principles distilled from the alumni concept experience, which summarize the current wisdom regarding development of a community which will serve as the »intelligence pool« for Diaspora Virtual University. Different types of remittances, as well as pessimistic and optimistic perspectives on remittances, are analyzed in the paper, and recommendations are summarized for current and future policy makers. Recognizing diaspora as a valuable foreign investor a model of partnership through the Serbian Regional Chambers of Commerce is also proposed.